The Effect Of Promotions And Discounts On Impulse Buying Of Nivea Products In Instagram Advertising With Positive Emotion As An Intervening Variable: (Case Study of Nivea Product Purchasing Decisions in the Madiun Community) - Rizal Ula Ananta Fauzi; Devi Sulistia Ningrum; Dian Citaningtyas Ari Kadi (Citakonsultindo, 2026)
Impulse buying refers to unplanned consumer purchases triggered by emotional or situational stimuli. This study investigates the effect of promotions and discounts on impulse buying behavior, with positive emotion as a mediating variable. Using a purposive sampling method, the study surveyed 385 respondents from Madiun City who had purchased Nivea body lotion at least twice. A quantitative approach was employed, with data collected through questionnaires and analyzed using SPSS version 16. The findings reveal that promotions and discounts significantly influence positive emotions, which in turn significantly affects impulse buying. Moreover, positive emotion mediates the relationship between promotions, discounts, and impulse buying behavior